Asymptotic profiles of positive steady states for a diffusive predator–prey model with predator interference. (February 2023) - Dong, Yaying; Li, Shanbing
Abstract: This paper is concerned with positive steady states for a diffusive predator–prey model with predator interference in a spatially heterogeneous environment. We first establish the necessary and sufficient conditions for the existence of positive steady states. In order to get a better understanding of the structure of positive steady states, we further investigate the asymptotic profiles of positive steady states as some parameter tends to zero or infinity.